الرقية الشرعية أحكامها وضوابطها د ا رسة فقهية - ملوكة, تبر; عرباوي, خنساء أم كلثوم; معمري, هناء (University of Eloued-جامعة الوادي, 2015)
تناول هذا البحث موضوع الرقية الشرعية أحكامها و ضوابطه ا د ا رسة فقهية, وذلك بتتبع واستق ا رء جزئيات هذا الموضوع في ثنايا الكتب. وقد قسّم إلى أربعة مباحث, فكان الأول منها يختص بمفهوم الرقية, أمّا الثاني فتعمّق بأنواعها, والثالث منها تضمن ضوابط الرقية ووسائمها, وبعض النتائج لحالات رُقيت, أما ال ا ربع والأخير فقد تناولنا فيه مسائل مختمفة حول الرقية, مستندين فيه إلى بعض أقوال الفقهاء من القدامى والمعاصرين, وقد استخمصنا من ذلك بعض النتائج القيمة التي أوردناها في . Summary Of The Research This research has dealt with the legal spell (roquia).its termsand controls as a doctrinal. Study through the scrutiny and induction of this topic's details within the books. It has been divided into four sections. The first one is about the concept of the spell. The second one is about its kinds. The third one is about it is controls and means and some results of cases that were spelled. In the fourth and the last one we have dealt with various issues about the legal spell relying on some of the sayings of the ancient and modern scholars and we have deduced some valuable results that we have mentioned in theconclusion.
مذكرة ليسانس
Keywords: الرقية الشرعية/أحكامها وضوابطها; Ruqyah Sharia/ses décisions et contrôles